Legality Constraints: The Emergence of a Dual Market for Tropical Timber Products? - Masiero, M.; Pettenella, D.; Cerutti, P.O. (MDPI, 2015)
The European Union (EU), the United States of America (USA), and Australia have adopted specific measures to avoid the placing of illegal timber on their markets. These measures might encourage the diversion of timber products from traditional large importers to destinations with a less stringent regulatory framework. During 2001–2013, the international trade in tropical primary timber products (logs; sawnwood; veneers and plywood) decreased by 13% in volume and increased by almost 5% in value. Imports by Australia, the EU, and the USA halved, while those by emerging economies such as China and India initially remained stable and later increased. Tropical timber products—mostly logs and sawnwood—might have been diverted towards emerging economies over the period considered. This general trend is confirmed when analyzing imports from countries that are implementing voluntary partnership agreements (VPA) within the EU Forest Law Enforcement, Governance and Trade (FLEGT) Action Plan. Several factors might influence these market dynamics, including changes induced by the 2008 financial crisis and the increasing domestic demand for timber products by emerging nations. The effects of legality measures on market trends are still unclear. Nonetheless, they might have encouraged uncertainty with regards to traditional importers and favored emerging ones.